Proteomic Analysis of Listeria monocytogenes FBUNT During Biofilm Formation at 10°C in Response to Lactocin AL705 - Melian, Constanza; Castellano, Patricia; Segli, Franco; Mendoza, Lucía M.; Vignolo, Graciela Margarita (Frontiers in Microbiology, 2021)
Listeria monocytogenes is one of the major food-related pathogens and is able to survive and multiply under different stress conditions. Its persistence in industrial premises and foods is partially due to its ability to form biofilm. Thus, as a natural strategy to overcome L. monocytogenes biofilm formation, the treatment with lactocin AL705 using a sublethal dose (20 AU/mL) was explored. The effect of the presence of the bacteriocin on the biofilm formation at 10°C of L. monocytogenes FBUNT was evaluated for its proteome and compared to the proteomes of planktonic and sessile cells grown at 10°C in the absence of lactocin. Compared to planktonic cells, adaptation of sessile cells during cold stress involved protein abundance shifts associated with ribosomes function and biogenesis, cell membrane functionality, carbohydrate and amino acid metabolism and transport. When sessile cells were treated with lactocin AL705, proteins up-regulation were mostly related to carbohydrate metabolism and nutrient transport in an attempt to compensate for impaired energy generation caused by bacteriocin interacting with the cytoplasmic membrane. Notably, transport systems as β-glucosidase IIABC (lmo0027), cellobiose (lmo2763) and trehalose (lmo1255) specific PTS proteins were highly overexpressed. In addition, mannose (lmo0098) specific PTS protein indicating the adaptive response of sessile cells to the bacteriocin was downregulated as this PTS system act as a class IIa bacteriocin receptor. A sublethal dose lactocin AL705 was able to reduce the biofilm formation in L. monocytogenes FBUNT and this bacteriocin induced adaptation mechanisms in treated sessile cells. These results constituting valuable data related to specific proteins targeting to control L. monocytogenes biofilm upon bacteriocin treatment.